Peningkatan Motivasi Dan Hasil Belajar Materi Lembaga Pemerintahan Desa Dan Kecamatan Melalui Penerapan Model Pembelajaran Word Square Pada Siswa Kelas IV SD 2 Getassrabi - Edy Murwanto (Universitas Muria Kudus, 2018)
Based on the results of the observations on the initial conditions in the 4th grade of SD 2 Getassrabi, the motivation and student learning outcomes of the village and sub-district governments were still very low. Student learning motivation is only 30% with completeness of learning outcomes only 40%. Therefore to improve this, research was carried out by applying the Word square learning model. And the results obtained after carrying out research for two cycles were student learning motivation increased to 80%, and learning completeness by 90%.